PENGARUH MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR SISWA PADA MATERI GAYA DI SEKITAR KITA DI KELAS IV SD NEGERI 49 BANDA ACEH - Nurul Amelia; Tursinawati; Fitri, Aida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is that the learning outcomes of fourth-grade students in the subject of force are still not optimal. The lack of application of learning models and interactive learning media causes the material not to be delivered optimally and has an impact on student learning outcomes, so it is necessary to apply a learning model that can increase student activity and understanding. This study aims to determine the effect of the cooperative learning model of the Teams Games Tournament (TGT) type assisted by snakes and ladders media on the learning outcomes of fourth-grade students in the subject of force in SD Negeri 49 Banda Aceh.The approach used in this study is a quantitative approach with a pre-experimental research type. The research design used is One Group Pretest–Posttest Design. This research was conducted in fourth-grade students of SD Negeri 49 Banda Aceh. The research sample consisted of all fourth-grade students who were used as the experimental class. The research instrument used was a test of learning outcomes of the science given before the treatment, namely the pretest and after the treatment, namely the posttest. Data analysis techniques were performed using the SPSS program, including normality tests, hypothesis testing using paired sample t-tests, The results of the hypothesis test indicate a significance value <0.05, so H₀ is rejected and Hₐ is accepted. So it can be concluded that there is a significant influence of the cooperative learning model of the Teams Games Tournament (TGT) type assisted by snakes and ladders media on student learning outcomes on the material of forces around us in grade IV of SD Negeri 49 Banda Aceh. The results of this study indicate that the cooperative learning model of the Teams Games Tournament (TGT) type assisted by snakes and ladders media can be used as an alternative to science learning to improve student learning outcomes and activity. Keywords: Kooperatif Tipe Teams Games Tournament, snakes and ladders, science learning outcomes